Comparative Study on Some Productive Traits of Muscovy and Sudani Ducks in Egypt - El-Samee , Laila D. Abd; El-Allawy, Hewida M.H.; Maghraby, Nagwa A. (International Journal of Poultry Science, 2012)
To evaluate the productive performance of Sudani ducks (local breed) in comparison with Muscovy ducks (imported breed) this experiment was conducted during summer season in Egypt. A total number of 24 Sudani (Cairina moschata) and 24 Muscovy (Cairina moschata) ducklings (3 weeks old) were used in this study, to evaluate some productive traits including growth performance and carcass characteristics. The results revealed that body weight gain of Muscovy breed was significantly higher by 27.22% than Sudani breed at 3-12 weeks of age. Meanwhile, Muscovy ducklings consumed more feed at 3-12 weeks of age than Sudani breed. Feed conversion was better in Muscovy (4.37) than Sudani (5.25) ducks. The results also indicated that percentage of inedible parts and dressing and deboning percentage were approximately similar in both breeds. Percentage of giblets in Sudani ducks was significantly higher than in Muscovy, while percentage of carcass fat, breast and drumsticks were significantly higher in Muscovy compared to Sudani ducks. Moisture percentage was higher (p<0.05) while ether extract and ash percentages were lower (p<0.05) in breast and leg meat of Muscovy ducks as compared to Sudani ducks. Protein percentage in breast and leg meat was similar in the two breeds. It is concluded that Muscovy ducks had better productive performance than Sudani ducks. Moreover, Muscovy ducks had higher percentages of carcass fat, breast and drumsticks than Sudani ducks. Meat of Sudani ducks is characterized by its lower percentage of moisture with higher percentages of ether extract and ash than meat of Muscovy ducks.